Deficiency of object-based attention specific to the gaze cue is independent of top-down attentional strategies. (May 2023) - Eito, Hirokazu; Wakabayashi, Akio
This study investigated whether modes of attentional selection (location-based or object-based) are modulated by the cue type, specifically social cues such as eye gaze and pointing fingers, or by a non-social cue, such as an arrow. Earlier studies have demonstrated that the object-based attention effect was found only with arrow cues when presenting a spatial cue at either end of a rectangle: gaze cues did not yield object-based facilitation. We examined whether this deficiency of object-based attention is generalized to social cues such as pointing fingers. We measured the reaction times to the target at each cued location, an opposite side of a cued location in the same object, or the location in a different object equidistant from the cued location for each cue. Results indicated that only the gaze cue weakened the object-based attention effect, even under the condition of participants' voluntary extension of their attentional focus. The pointing cue induced sufficient object-based facilitation, as did the arrow cue. These results suggest that the deficiency of object-based attention was observed only for the gaze cue, and that it would be caused by a factor that is unique to the gaze cue, which narrows the attentional focus.